Determinan Terhadap Keputusan Pembelian Lipstik Wardah Di Shopee - Fitri Ngumdatul Robikah; Deni Ramdani (Pusat Riset dan Inovasi Nasional, 2023)
This research was conducted to find out whether product attributes, service quality, and electronic word of mouth affect purchasing decisions for Wardah Liptrik at Shopee. This research is a quantitative research. The sample of this research is Shopee application users who have made transactions more than once on applications that are distributed to 100 respondents. Data analysis was performed using multiple linear analysis techniques which were processed using the SPSS data processing application version 25. The results showed that product attributes and service quality had an effect on purchasing decisions, but the EWOM variable had no effect on purchasing decisions. The results provide managerial implications for business people to add product attributes and improve service quality in order to increase consumer repurchase interest. With increasing purchasing decisions, it is expected that a business that is run can develop and be sustainable.